Cardiothoracic Area Ratio Predicts Lethal Pulmonary Venous Obstruction in Patients with Single Ventricle and Total Anomalous Pulmonary Venous Connection - Emi, Misugi; Inamura, Noboru (American Journal of Perinatology Reports, 2018)
Background and Objectives When single ventricle (SV) is complicated with total anomalous pulmonary venous connection (TAPVC), the pulmonary vein obstruction (PVO) occurs at a high rate.There are some patients who died from the lethal PVO (l-PVO) which needed PVO release dead due to severe desaturation within 24 hours after birth. The purpose of this study was to find a predictive marker for l-PVO during the fetal period.Methods We enrolled 21 patients diagnosed with SV associated with TAPVC in the antenatal period. Ten patients had supracardiac, five had cardiac, five had infracardiac, and one had mixed TAPVC. We reviewed fetal echocardiography and measured cardiothoracic area ratio (CTAR) and total cardiac dimension (TCD). We divided 21 cases into l-PVO group (6) and non-l-PVO group (15) and compared the fetal echocardiography findings and postnatal prognoses between the groups.Results CTAR at the final fetal echocardiography was 16 to 29% (median: 21) in the l-PVO group and 22 to 38% (median: 28) in the non-l-PVO group (p = 0.01). TCD/week at the final echocardiography was 0.67 to 1.0 (median: 0.77) in the l-PVO group and 0.78 to 1.2 (median: 0.96) in the non-l-PVO group (p = 0.02).Conclusion Reduced CTAR in the antenatal period is a good predictor of l-PVO after birth.
Keywords: pulmonary venous obstruction; single ventricle; TAPVC; Fetal echocardiography; CTAR